1998
DOI: 10.1029/97jd03374
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the sporadic Na layers observed during the Airborne Lidar and Observations of Hawaiian Airglow/Airborne Noctilucent Cloud (ALOHA/ANLC‐93) campaigns

Abstract: Abstract. We summarize the characteristics of the 43 sporadic Na (Na0 layers observed by the airborne Na density and the Haleakala Na wind/temperature lidars during the Airborne Lidar and Observations of Hawaiian Airglow/Airborne Noctilucent Cloud (ALOHA/ANLC-93) campaigns. Na• layers are clearly not a local phenomenon since the horizontal extents varied from approximately 25 to almost 1600 km with a mean of 440 km. For the majority of the Na• layers observed above Haleakala, the temperatures were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 34 publications
8
44
0
Order By: Relevance
“…An airborne lidar (ALOHA90) has also been used to show that an SSL in the Pacific equatorial region extended for more than 1800 km (Kane et al, 1991). Another airborne observation (ALOHA/ANLC-93) showed that the horizontal extents varied from approximately 25 to almost 1600 km with a mean of 440 km (Qian et al, 1998). Recently, satelliteborne measurements illustrated that most SSLs were much more prevalent in the Southern Hemisphere, with a horizontal extent of less than 300 km (Fan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An airborne lidar (ALOHA90) has also been used to show that an SSL in the Pacific equatorial region extended for more than 1800 km (Kane et al, 1991). Another airborne observation (ALOHA/ANLC-93) showed that the horizontal extents varied from approximately 25 to almost 1600 km with a mean of 440 km (Qian et al, 1998). Recently, satelliteborne measurements illustrated that most SSLs were much more prevalent in the Southern Hemisphere, with a horizontal extent of less than 300 km (Fan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More extensive studies on SSLs by lidars were conducted after the observation by Von Zahn and Hansen (1988) (e.g. Kwon et al, 1988;Batista et al, 1989;Senft et al, 1989;Kane et al, 1991;Gardner et al, 1993;Clemesha, 1995;Clemesha et al, 1998;Qian et al, 1998;Gong et al, 2002;Clemesha et al, 2004;Williams et al, 2006Williams et al, , 2007Fan et al, 2007;Nesse et al, 2008;Vishnu Prasanth et al, 2007;Yi et al, 2007;Heinrich et al, 2008). Sporadic sodium layers have been studied for more than 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Still, a strong link between the neutral and the ionized sporadic metal layers is generally assumed (e.g. Alpers et al, 1993;Qian et al, 1998). For the case of Ca atoms and Ca + ions, this link can be studied time-resolved by ground-based lidar observations.…”
Section: Introductionmentioning
confidence: 99%
“…Clemesha et al (1999) mentioned that the median value was about 420 km as a typical horizontal dimension at São Jose dos Campos. SSLs that extended farther than 1000 km were also observed by an airborne lidar (e.g., Kane et al, 1991;Gu et al, 1995;Qian et al, 1998). SSLs have concentrations about 2-10 times higher than that of the background normal sodium layer (cf.…”
Section: T Takahashi Et Al: Generation Mechanisms Of Ssl In the Polmentioning
confidence: 99%